Effect of supplemental irrigation on yield and water productivity of dry season crops in Andaman and Nicobar Islands - RAJA, R; RAVISANKAR, N; CHAUDHURI, S GHOSHAL; AMBAST, S K; CHAND, SUBHASH; DIN, M; MEENA, BABULAL; SUBRAMANI, T; AHMED, ZAMIR (The Indian Journal of Agricultural Sciences, 2012)
Field experiments were conducted with different supplemental irrigation levels for growing maize, greengram, sesame, okra and chilies during the dry season of 2006–07 and 2007–08 in A & N Islands. The results indicated that though the yields achieved with supplemental irrigation has not achieved at par with that of farmers, practice (I5) of irrigating the crop as and when required (4 160 and 10 398 kg/ha during 2006–07 and 2007–08 respectively), it has increased the yield significantly in both the years vis-à-vis I0 i e, no irrigation (1 355 and 5 640 kg/ha during 2006–07 and 2007–08 respectively). The percent yield increase over I0 when supplemental irrigation was provided one (I1), two (I2), three(I3) and four (I4) times due to supplemental irrigation was 48, 95, 133 and 178 in I1, I2, I3 and I4 during 2006–07 and 13, 27, 53, 62 in I1, I2, I3 and I4 during 2007–08 respectively. Thus by providing supplemental irrigation at different critical crop growth stages, higher yield and economic returns were achieved with lesser irrigation water usage, an important consideration for raising dry season crops in the rice fallows from the harvested rainwater of rainy season under Island conditions. However, the results also underlined the fact that cultivation of vegetables like okra and chillies on residual soil moisture alone without irrigation during dry season in the islands may be riskier and result in economic loss if the rainf all during the cropping period is very low.